2021
DOI: 10.1186/s40658-021-00364-9
|View full text |Cite
|
Sign up to set email alerts
|

Standard MRI-based attenuation correction for PET/MRI phantoms: a novel concept using MRI-visible polymer

Abstract: Background PET/MRI phantom studies are challenged by the need of phantom-specific attenuation templates to account for attenuation properties of the phantom material. We present a PET/MRI phantom built from MRI-visible material for which attenuation correction (AC) can be performed using the standard MRI-based AC. Methods A water-fillable phantom was 3D-printed with a commercially available MRI-visible polymer. The phantom had a cylindrical shape a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Systematic underestimation of SUV in bone tissue or lesions close to the bone of >10% compared to PET/CT has been described [ 60 , 62 ], whereas SUV differences were <5% in other normal tissues [ 60 ]. It should also be noted that cross-calibration of PET/MRI scanners is generally hampered by water-filled phantoms, which are commonly used for SUV calibration in PET/CT and can produce substantial artifacts in the MR-AC sequence with corresponding SUV errors [ 63 , 64 ]. In such phantoms, inter-vendor differences in MR-AC maps [ 61 ] can lead to SUV differences in phantom spheres of 10–20% [ 58 ].…”
Section: Factors Affecting Pet Quantificationmentioning
confidence: 99%
“…Systematic underestimation of SUV in bone tissue or lesions close to the bone of >10% compared to PET/CT has been described [ 60 , 62 ], whereas SUV differences were <5% in other normal tissues [ 60 ]. It should also be noted that cross-calibration of PET/MRI scanners is generally hampered by water-filled phantoms, which are commonly used for SUV calibration in PET/CT and can produce substantial artifacts in the MR-AC sequence with corresponding SUV errors [ 63 , 64 ]. In such phantoms, inter-vendor differences in MR-AC maps [ 61 ] can lead to SUV differences in phantom spheres of 10–20% [ 58 ].…”
Section: Factors Affecting Pet Quantificationmentioning
confidence: 99%
“…In their systematic review to identify trends in the use of 3D printing in the development of medical imaging phantoms, Fillipou and Tsoumpas [ 32 ] found that radiological properties are not commonly tested by manufacturers for 3D printing. However, Rausch et al [ 33 ] have recently created a phantom using 3D printed polymer RGD252 (Stratasys), previously demonstrated as MRI visible [ 34 ], that is visible in both modalities for simultaneous PET/MRI acquisitions.…”
Section: Materials In Phantom Designmentioning
confidence: 99%
“…Rausch et al [ 33 ] demonstrated the first PET/MRI phantom in-house-made with MRI visible housing. The cylindrical phantom had rod features on the bottom lid, whilst keeping the top section of the phantom homogenous.…”
Section: Geometric and Homogeneous Phantomsmentioning
confidence: 99%
See 1 more Smart Citation
“…While substantial progress has been made in manufacturing phantoms capable of mimicking both electron density and MRI contrast characteristics of human tissues (7)(8)(9), no such phantom that could be used to assess the performance of multiple MR-based AC techniques is yet widely available. Additionally, water-filled phantoms, a mainstay in the accreditation of PET scanners (10), produce resonance artifacts in MR images (11).…”
Section: Introductionmentioning
confidence: 99%